CLAIM RESERVE ESTIMATION WITH THE EFFECT OF IBNR CLAIMS USING STATE-SPACE EQUATION METHOD - Hansel Soepinto, Owen
This study examines a method to estimate claim reserves that uses state-space equation and also the effect of IBNR claims to claim reserves. Direct benefit of such method is the ability to implement Kalman Filter algorithm. This algorithm is well-used for this case because it is fast to comprehend the condition of a state within a state-space system, which its true value cannot be observed, based on the observations obtained for each state. Parameters of the model is estimated by using EM algorithm, and only after that, Kalman Filter algorithm is applicable. To be able to calculate claim reserves, this study also uses runoff triangle as the first step of transforming raw data. This study also compares the prediction given by state-space method with the prediction given by chain ladder method. The result of this study is quite surprising since both method gives relatively similar estimation. However, state-space equation is recommended because of its ability to oversee IBNR effect on claim data.